Identification of the Memory Kernels and Controllability for Parabolic Equations (European Journal of Pure and Applied Mathematics, 2010)
This paper deals with the controllability and observability properties of the mathematical models models (describing systems with thermal memory) consisting of boundary value problems of parabolic type, where the differential equation contains additional integralexpressions including ``memory functions" which describe thememory property of the material. The proof of controllabilityrelies on a Carleman type estimate and duality arguments.